Optimizing Raw Material Inventory Using the EOQ Method (Business Case “Madumongso Bu Binti” - Wahyuningsih, Diah Ayu; Fauji, Diah Ayu Septi (Universitas Nusantara PGRI Kediri, 2024)
Research aim : This research aims to analyze the most economical number of orders for sticky rice raw materials to fulfill supplies at the